Leasing in Russian agricultural economy: current stage of development - A. A. Kiritsa (Управление)
The purpose of the study is to analyze leasing sustainable development as the main investment mechanism of the Russian agrarian sector technical re-equipment.   The author uses general scientific methods (analysis and synthesis, economic and statistical methods, graphical methods, etc.). The current state of the domestic agrarian sector technical equipment, the development of agricultural machinery leasing market development, issues and prospects for the use of agrarian leasing at the present stage have been considered. Considering the current situation in the domestic market, decreased prices for agricultural products and outstripping growth of prices for equipment, domestic agricultural producers need systemic state support to maintain the machinery and tractor fleet renewal pace. In conditions of agricultural machinery and investment resources for its reproduction deficit, leasing is one of the effective tools in solving the technical potential of the agricultural sector technical potential strengthening issues. The main promising areas of leasing mechanisms application, contributing to technical re-equipment acceleration in the agricultural sector have been proposed (sustainable development projects, national “green taxonomy”, “green” bonds; agricultural machinery market digitalization development; use of leasing mechanisms for the machinery and technology complexes development as a modern form of joint machinery use in agriculture). The proposed areas will ensure systemic development and acceleration of Russian agrarian sector technical re-equipment.